Persepsi Mayarakat terhadap Pembentukan Citra Merek: - Amirah Shinta Permatasari; Heidy Arviani (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
This study aims to determine the public's perception of creating a brand image in collaboration with PT. Lemonilo with NCT DREAM as Brand Ambassador. The Lemonilo company is collaborating with NCT DREAM as a Brand Ambassador which is part of a company promotion that is carried out with the aim of building and creating a brand image for the Lemonilo company. Lemonilo is collaborating with the boy group NCT DREAM who has a good personality, good image, and is also on the rise in Indonesia and South Korea. The research approach used in this research is qualitative research with a qualitative descriptive approach. Researchers use in-depth interviews or in-depth interviews. This method is used to obtain data on public perception of brand image formation in PT. Lemonilo Indonesia's collaboration with NCT DREAM as a brand ambassador. Based on the results of the analysis, the researcher found that each informant had various perceptions of brand image formation in the collaboration of PT. Lemonilo Indonesia with NCT DREAM as Brand Ambassador. In the formation of a perception, of course, the background is the existence of a frame of reference and a field of experience so that each individual can provide his own perception of what he receives and sees. With this collaboration that exists between Lemonilo and NCT DREAM, you will continue to imagine NCT DREAM in Lemonilo noodles because you feel proud that the two of you can make such an extraordinary collaboration.